PGC-1α Promotes mitochondrial biosynthesis and energy metabolism of goose fatty liver - Jiahui Li; Mengqing Lv; Zijin Yuan; Jing Ge; Tuoyu Geng; Daoqing Gong; Minmeng Zhao (Poultry Science)
To investigate the functions of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) in the goose fatty liver, a total of 30 healthy 63-day-old male Landes geese were selected and randomly assigned to control group and overfeeding group. The overexpression or RNA interference assay of PGC-1α was performed in goose primary hepatocytes. Our data showed that the PGC-1α expression was increased in fatty liver. The abundance of mitochondrial biosynthesis-related and energy metabolism-related genes, including mitochondrial transcription factor A (TFAM), mitochondrial transcription factor B1 (TFB1M), mitochondrial transcription factor B2 (TFB2M), nuclear respiratory factor 1 (NRF1), DNA topoisomerase I mitochondrial (TOP1MT), peroxisome proliferator-activated receptor gamma coactivator 1-beta (PGC-1β), sirtuin 3 (SIRT3), mitochondrially encoded cytochrome B (CYTB), and AMP-activated protein kinase alpha (AMPKα) were significantly increased in fatty liver. The abundance of TFAM, TFB1M, TFB2M, NRF1, and TOP1MT transcript was induced by PGC-1α overexpression, but inhibited by PGC-1α interference in primary hepatocytes. The mRNA expression levels of PGC-1β, SIRT3, SIRT5, CYTB, and AMPKα were significantly enhanced after PGC-1α overexpression. However, the mRNA expression levels of PGC-1β, SIRT5 and AMPKα were decreased after PGC-1α interference. Furthermore, we observed a significant increase in the mitochondrial DNA (mtDNA) copy number, the activity of mitochondrial respiratory chain complex Ⅳ (MRCC Ⅳ), succinate dehydrogenase (SDH), malate dehydrogenase (MDH), and the NAD+/NADH ratio in fatty liver. But the activity of MRCC Ⅴ, as well as the levels of ADP and ATP in fatty liver were reduced. Additionally, the mtDNA copy number, the activity of MRCC Ⅰ, MRCC Ⅲ-Ⅴ, SDH, and MDH, and NAD+/NADH ratio were enhanced by PGC-1α overexpression; Whereas the mtDNA copy number, the activity of MRCC Ⅰ, SDH, and MDH, and the ratio of NAD+/NADH were inhibited by PGC-1α interference. In conclusion, these findings suggest that PGC-1α improves mitochondrial biosynthesis and energy metabolism in goose fatty liver, which may be an adaptive mechanism for goose fatty liver to cope with steatosis.